STRATEGI PELESTARIAN BUDAYA LOKAL SEBAGAI UPAYA PENGEMBANGAN PARIWISATA BUDAYA (SEBAUAH ANALISIS TEORITIS) - Desrika Talib; Sri Sunarti (Tulisan Ilmiah Pariwisata (TULIP), 2021)
This research aims to analyze the strategy of preserving local culture to develop cultural tourism. This study is a form of strategic assessment effort to find solutions in the development of tourist destinations, especially cultural tourism. This study used the literature review method by collecting several references from previous research related to tourism development and preservation strategies. From the results of the analysis, it was found that one form of strategy that needs to be done is a marketing strategy to increase the number of tourist visits by creating a branding of cultural tourist attractions as a quality tourist attraction, maintaining the culture or customs and characteristics of local communities, conducting promotions via the internet or through the internet. brochures to introduce cultural tourist attractions to be better known by tourists, as well as build an image of tourist attractions to fix problems that result in a decreased number of visits